An Argumentative Discourse Analysis of the Newspaper Editorial “The 9/30 Tragedy” - Rahman, Mustafa A. (Jurnal Ilmiah Peuradeun, 2024)
Academic studies on newspaper discourse have focused primarily on the structure of news items. Research on an argumentative discourse of newspaper editorials is understudied. By using the sociocognitive theory of knowledge and opinion as the theoretical basis, this article aims to analyze the argumentative discourse constructed in “The 9/30 Tragedy” editorial published in The Jakarta Post and to discuss whether the arguments in the text constitute knowledge or solely opinions of the editorial team on the defunct Indonesian Communist Party (PKI). The eclectic research method used the pragma-dialectical model of argumentation supported by intertextuality and vocabulary analysis. The findings reveal that the editorial has a standpoint that the tragedy of September 30, 1965, has led the course of Indonesia’s history for the worst tragedy and that the argumentation is manifested in three stages: confrontational stage, argumentation stage, and concluding stage. Acting as the protagonist, the editorial team maneuvers strategically by quoting other voices and using an evaluative lexical repertoire to support their arguments criticizing Soeharto’s leadership legacy. Overall, the editorial seems to reconstruct mental models for the readers by questioning the reliability of the military-dictated textbooks about the 9/30 Tragedy, thereby reshaping the historical knowledge about the calamity, which is justifiable.